2006
DOI: 10.1039/b606507b
|View full text |Cite
|
Sign up to set email alerts
|

Solid state NMR studies of photoluminescent cadmium chalcogenide nanoparticles

Abstract: Solid state (113)Cd, (77)Se, (13)C and (31)P NMR have been used to study a number of Cd chalcogenide nanoparticles synthesized in tri-n-octyl-phosphine (TOP) with different compositions and architectures. The pure CdSe and CdTe nanoparticles show a dramatic, size-sensitive broadening of the (113)Cd NMR line, which can be explained in terms of a chemical shift distribution arising from multiple Cd environments. From (13)C NMR, it has been discovered that TOP, or its derivatives such as TOPO (trioctylphosphine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
147
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(168 citation statements)
references
References 33 publications
21
147
0
Order By: Relevance
“…34 Previously we also reported solid-state NMR studies of the synthesis-structure-property relationship of ternary-alloyed regular QDs of CdTeSe with TOP capping agents and ZnCdS regular QDs with stearic acid capping agents. 28,35 The interactions of the surface ligand and surface Cd atoms were identified, together with the structural information of the ternary core, namely homogeneously alloyed vs gradiently alloyed. To the best of our knowledge, our solidstate NMR identification of such structural information of ternary QDs, including the surface environment and inner chemical composition, was the first.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Previously we also reported solid-state NMR studies of the synthesis-structure-property relationship of ternary-alloyed regular QDs of CdTeSe with TOP capping agents and ZnCdS regular QDs with stearic acid capping agents. 28,35 The interactions of the surface ligand and surface Cd atoms were identified, together with the structural information of the ternary core, namely homogeneously alloyed vs gradiently alloyed. To the best of our knowledge, our solidstate NMR identification of such structural information of ternary QDs, including the surface environment and inner chemical composition, was the first.…”
Section: Resultsmentioning
confidence: 99%
“…20 nm of the bandgap emission is dramatically smaller than the smallest value of 35 nm claimed (but typically 50 -60 nm in the spectra shown) previously for a ternary-alloyed CdTeSe regular QD ensemble synthesized by a 300°C hot-injection approach. 27,28 It is worthy of notice that homogeneous fluorescence linewidths of different semiconductor nanocrystals are different; CdSe and PbS single dots exhibit ca. 10 nm 4 and 50 nm 24 fluorescence line widths with homogeneous broadening, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…signifies Cd atoms at the surface in a broad range of different disordered coordination environments. [30] Such broad Cd spectra have previously been observed for Cd-rich surfaces in CdS NPs (0 to -750 ppm).…”
mentioning
confidence: 89%
“…Such experimental observation is in line with our previous work on pure bulk CdSe (shift −474 ppm, halfwidth 177 Hz) and a bulk CdSeS (60:40) alloy (shift −481 ppm, halfwidth 1617 Hz) which showed that introducing S causes a shift to more negative values and a broadening of the line. 38 Further negative shifting relative to the bulk seems to be a feature of the NCs. Furthermore, a 77 Se CP signal could not be found, which might be expected if there are very few Se atoms in the surface region for 1 H to cross-polarize to.…”
mentioning
confidence: 99%